Pengaruh Media Monopoli Baper Terhadap Aktivitas Dan Hasil Belajar Peserta Didik Kelas Viii Di Smpn 9 Surabaya - Shalma Esti Nur Widyasari; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2023)
In Pancasila and Civic Education, students required be creative and active in developing themselves and knowledge. Reality, implementation of Pancasila and Civic Education students still tend passive and easily bored,,in SMP Negeri 9 Surabaya, Pancasila and Civic Education subjects are quite difficult to understand because they have a lot of material to remember and it is quite difficult for students to remember and memorize the articles in the law. act. The use of learning media can solve the problem of the diversity of student learning styles, make it easy for teachers to convey messages, and encourage students to learn. In this study, learning media used the Baper monopoly game media (Learning Legislation) in learning laws and regulations. The type of research that has been used in this research is quantitative research, quasi-experimental type, with two groups (experimental and control). This research was conducted at SMP Negeri 9 Surabaya which were selected using random sampling, the samples in this study were students in class VIII A (experimental class) and class VIII B (control class). The data collection technique in this study is a matter of tests. While the data analysis technique uses a different test using the t test technique. The results showed that the learning activities of the experimental class were in the very good category with a percentage of 79.45%, while the control class was in the adequate category, such as cone theory. Edgar Dale's experience is that the more learning media variables, the more activities carried out by students and the level of involvement of students. starting from visual, oral, writing, to motor, so the material that students understand reaches 90%. As well as having a significant influence on the use of monopoly media on student learning outcomes in the material Interpreting Legislation - Invitations, namely the results of the t test, the 2-tailed significance value gets the result 0.000 <0.05 which states Ho is rejected and Ha is accepted, supported by a comparison of the class average posttest scores the experiment was bigger than the control class, namely 67 > 62. Keywords: Baper Monopoly, Learning Activities, Learning Outcomes